Characterization of indoor air quality in relation to ventilation practices in hospitals of Lahore, Pakistan - Nimra, Afzal; Ali, Zulfiqar; Ahmad Nasir, Zaheer; Tyrrel, Sean; Sidra, Safdar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Temporal variations of particulate matter (PM) and carbon dioxide (CO2 ) in orthopedic wards and emergency rooms of different hospitals of Lahore, Pakistan were investigated. Hospitals were classified into two groups, I (centrally airconditioned) and II (non-central air-conditioned) based on the ventilation system. Statistical analysis indicated significantly lower PM and CO2 levels in centrally air-conditioned hospitals in comparison to non-central air-conditioned. The low indoor-outdoor (I/O) ratio of PM2.5 in the ward and emergency rooms of group I (0.62, 0.45) as compared to group II (0.70, 0.83), respectively, suggested that indoor spaces equipped with central air-conditioning systems efficiently filter particulates as compared to non- central air conditioning systems. Apart from the ventilation type, increased visitor and doctors’ activities, and cleaning sessions were observed to contribute significantly to indoor air quality. This study adds up to the understanding of temporal variations in PM emissions and the role of ventilation systems in context of hospitals in the urban centers in Pakistan. The findings can inform the development of intervention strategies to maintain the appropriate air quality in health care built environment in developing countries.